2018
DOI: 10.1124/dmd.118.082073
|View full text |Cite
|
Sign up to set email alerts
|

S-Enantiomer of 19-Hydroxyeicosatetraenoic Acid Preferentially Protects Against Angiotensin II-Induced Cardiac Hypertrophy

Abstract: We had recently demonstrated that the racemic mixture of 19-hydroxyeicosatetraenoic acid (19-HETE) protects against angiotensin II (Ang II)-induced cardiac hypertrophy. Therefore, the purpose of this study was to investigate whether the orenantiomer of 19-HETE confers cardioprotection against Ang II-induced cellular hypertrophy in RL-14 and H9c2 cells. Both cell lines were treated with vehicle or 10 M Ang II in the absence and presence of 20M 19()HETE or 19()HETE for 24 hours. Thereafter, the level of midchain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 50 publications
3
26
0
Order By: Relevance
“…The K i values of both enantiomers showed that the S-enantiomer is more potent than the R-enantiomer by approximately 2.4-fold. This comes in agreement with our previous work demonstrating that the S-enantiomer of 19-HETE has a preferential effect over the R-enantiomer in inhibiting the formation of midchain HETEs (Shoieb and El-Kadi, 2018). In accordance with being noncompetitive inhibitors, the in vitro stability study showed that both enantiomers of 19-HETE are metabolically stable in solution during the 30-minute time course of the kinetic experiment as there was no significant difference in the level of both enantiomers in the duration of the experiment (Supplemental Figs.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The K i values of both enantiomers showed that the S-enantiomer is more potent than the R-enantiomer by approximately 2.4-fold. This comes in agreement with our previous work demonstrating that the S-enantiomer of 19-HETE has a preferential effect over the R-enantiomer in inhibiting the formation of midchain HETEs (Shoieb and El-Kadi, 2018). In accordance with being noncompetitive inhibitors, the in vitro stability study showed that both enantiomers of 19-HETE are metabolically stable in solution during the 30-minute time course of the kinetic experiment as there was no significant difference in the level of both enantiomers in the duration of the experiment (Supplemental Figs.…”
Section: Resultssupporting
confidence: 93%
“…1) protect against angiotensin II (Ang II)-induced cardiac hypertrophy with preferential effect of 19(S)-HETE. One important finding of our study was that both enantiomers of 19-HETE inhibited the formation of midchain HETEs and the catalytic activity of CYP1B1 in two different cell lines, human ventricular cardiomyocytes RL-14 cells and rat cardiomyoblasts H9c2 cells (Shoieb and El-Kadi, 2018). To obtain a comprehensive understanding of the protective role of R-and S-enantiomers of 19-HETE in the case of cardiac hypertrophy, we undertook the current study to examine, using 7-ethoxyresorufin O-deethylation (EROD) assay, the inhibitory effect of both enantiomers on human recombinant CYP1B1 enzyme.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Neither enantiomer of 19-HETE produced significant effects on mRNA or protein for CYP2B6, CYP2C8, or CYP2J2. The S-enantiomer increased CYP4F2 and CYP4F11 mRNA and protein expression levels (Shoieb and El-Kadi, 2018). The opposite roles of the EETs and HETEs suggest that the ratios between the two classes are important.…”
Section: Metabolismmentioning
confidence: 93%